Remove that Pyramid! studies on the archaeology and history of predynastic and pharaonic Egypt in honour of Stan Hendrickx - Claes, Wouter; Meyer, Marleen de 19-; Eyckerman, Merel 1981-; Huyge, Dirk 1957-2018 (Peeters, 2021)
This volume in honour of the career of Stan Hendrickx includes 47 contributions that deal with the archaeology and history of Predynastic and Pharaonic Egypt. Given the influential role that Stan Hendrickx plays on our current knowledge of the Predynastic and Early Dynastic periods, many of the articles cluster in that time frame and deal with topics in material culture, iconography, and archaeology of early Egypt (pottery, stone vessels, lithics, state formation, and rock art). Contributions covering the pharaonic period primarily consist of ceramic studies, another field of expertise of Stan Hendrickx. Several articles focus on sites such as Elkab, Dayr al-Barsha, Adaïma, and the Dakhla Oasis, where Stan Hendrickx has been involved as an archaeologist and a ceramologist.
Keywords: Funde; Archäologische Stätte; Ägypten -- Altertum; Aufsatzsammlung; Festschrift